PERSEPSI DAN RESPON PETANI TERHADAP KOMPONEN TEKNOLOGI JAJAR LEGOWO SUPER DI KABUPATEN TEGAL (JASEP, 2020)
Jajar legowo super is an integrated rice cultivation technology based on 2: 1 planting method. The main technology components applied in the super legowo row in Tegal Regency are new high yielding varieties with high yield potential (Inpari 32 and Inpari 33), biodecomposers given together with soil treatment, biological fertilizer as seed treatment, fertilizing according to recommendations, and controlling plant pests OPT) environmentally friendly. Jajar Legowo Super was introduced in Tegal Regency in 2018 in 8 districts namely: Dukuhwaru, Pagerbarang, Balapulang, Talang, Tarub, Pacing, Lebaksiu and Adiwerna. The study of perceptions and responses was carried out on 50 farmers in 8 sub-districts, besides capturing feedback, information on opportunities for sustainability from jajar legowo super technology was the main objective of this study. In general, farmers' perceptions of jajar legowo super reach a score of 2.47 (moderate / doubtful level of perception on a scale of 1-3). This is caused by the way of planting jajar legowo which is considered difficult to apply (score 1.87) by farmers. Farmer respondents were also doubtful because of the unavailability of the jarwo super technology components that were considered important by farmers, namely the Inpari 32 VUB seed, Agrimet for seed treatment, anaerobic biodecomposers and recommended vegetable pesticides. The response of farmers to the technology component is generally positive but the level of sustainability is low because it is difficult to get the technology component in the super legowo range. Farmers and officials suggest that the development of technological innovation should be balanced with the presence of these components in the field.